Independent and Joint Effect of Brachial-Ankle Pulse Wave Velocity and Blood Pressure Control on Incident Stroke in Hypertensive Adults. Issue 1 (July 2016) - Song, Yun; Xu, Benjamin; Xu, Richard; Tung, Renee; Frank, Eric; Tromble, Wayne; Fu, Tong; Zhang, Weiyi; Yu, Tao; Zhang, Chunyan; Fan, Fangfang; Zhang, Yan; et al.
Abstract : Pulse wave velocity (PWV) has been shown to influence the effects of antihypertensive drugs in the prevention of cardiovascular diseases. Data are limited on whether PWV is an independent predictor of stroke above and beyond hypertension control. This longitudinal analysis examined the independent and joint effect of brachial-ankle PWV (baPWV) with hypertension control on the risk of first stroke. This report included 3310 hypertensive adults, a subset of the China Stroke Primary Prevention Trial (CSPPT) with baseline measurements for baPWV. During a median follow-up of 4.5 years, 111 participants developed first stroke. The risk of stroke was higher among participants with baPWV in the highest quartile than among those in the lower quartiles (6.3% versus 2.4%; hazard ratio, 1.66; 95% confidence interval, 1.06–2.60). Similarly, the participants with inadequate hypertension control had a higher risk of stroke than those with adequate control (5.1% versus 1.8%; hazard ratio, 2.32; 95% confidence interval, 1.49–3.61). When baPWV and hypertension control were examined jointly, participants in the highest baPWV quartile and with inadequate hypertension control had the highest risk of stroke compared with their counterparts (7.5% versus 1.3%; hazard ratio, 3.57; 95% confidence interval, 1.88–6.77). There was a significant and independent effect of high baPWV on stroke as shown among participants with adequate hypertension control (4.2% versus 1.3%; hazard ratio, 2.29, 95% confidence interval, 1.09–4.81). In summary, among hypertensive patients, baPWV and hypertension control were found to independently and jointly affect the risk of first stroke. Participants with high baPWV and inadequate hypertension control had the highest risk of stroke compared with other groups. Abstract : Supplemental Digital Content is available in the text.